Strategi Brand Image Pada Rumah Makan Ayam Geprek Sai di Kabupaten Lamongan Prespektif Studi Kelayakan Bisnis Islam - Riris Trimaulida Rahmawati; Abdurrahman Abdurrahman (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This study focuses on the strategic brand image of Ayam Geprek Sai Lamongan Branch in the context of Islamic business. This research aims to understand the influence of Islam on consumer perceptions of a company's brand image and its impact on business success, financial performance and reputation. This study uses qualitative and descriptive research methods to analyze the brand image of Ayam Geprek Sai Lamongan Branch. This research focuses on studying the Islamic business environment in Lamongan Regency, especially Rumah Makan Geprek Sai. This research uses descriptive qualitative methods to collect data from restaurants and data sources collected through observations. This study contributes to the understanding of Islamic business feasibility studies and the potential that can contribute to company success.